QCT of the femur: Comparison between QCTPro CTXA and MIAF Femur - Wang, Ling; Museyko, Oleg; Su, Yongbin; Brown, Keenan; Yang, Ruopei; Zhang, Yong; Duanmu, Yangyang; Guo, Zhe; Zhang, Wei; Yan, Dong; Cheng, Xiaoguang; Engelke, Klaus (Bone, 2019)
QCT is commonly employed in research studies and clinical trials to measure BMD at the proximal femur. In this study we compared two analysis software options, QCTPro CTXA and MIAF-Femur, using CT scans of the semi-anthropometric European Proximal Femur Phantom (EPFP) and in vivo data from 130 Chinese elderly men and women aged 60-80 years.
CRIS-Team WoS Importer:2019-02-27